Development of Differentiated Learning Media Based on Google Sites on Earthquake Disaster Mitigation Material - Robat Widodo; Siti Asiyah; Budi Utomo (Geography Education Study Program, Faculty of Teacher Training and Education, 2026)
Xaverius 3 High School, based on student profile data, has different socio-cultural backgrounds, abilities and learning styles. There needs to be a differentiated approach that allows each learner to learn according to their learning abilities and style, thereby improving overall learning outcomes. Apart from that, it is known that geography is a subject in high school that requires visual, concrete and practical understanding to make it easier for students to digest. Based on preliminary studies, learning media based on Google Sites is needed which can be a solution for students to understand geographic material more concretely and be able to learn flexibly according to their needs and potential. Therefore, the research aims to develop differentiated learning media based on Google Sites that are valid, practical, and have a potential effect on students' learning outcomes. The development model used in this research is the Hannafin and Peck model which consists of three stages, namely: (1) needs analysis, (2) design, and (3) development and implementation. For product evaluation, researchers use Tessmer formative evaluation, with stages, namely expert review, one to one, small group, and fild test. This research has produced differentiated learning media products on earthquake disaster mitigation that are valid, practical, effective through expert review evaluations, one to one, small groups, and field tests. By using Google Sites-based learning media, students can learn more effectively and practically according to their learning needs. Keywords: Development, Media Google sites